Evaluación de los factores asociados a la mortalidad por tuberculosis activa durante la pandemia covid-19 en Loreto 2020-2021 - Gonzales Rengifo, Diana Gabriela (2023)
Objective: To evaluate the factors associated with mortality from active tuberculosis during the COVID-19 pandemic in Loreto 2020-2021. Methods: Observational, cross-sectional study of review of medical records. The database of patients of the SIGTB of the Geresa Loreto in the period of 2020-2021 was analyzed. The confidentiality and privacy of the data was respected, there was no access to identifying data. The analysis was performed using SPSS v25 software. Results: We analyzed 2943 data from the period 2020 to 2021, during the pandemic 31.1% of patients with COVID-19 died. The sociodemographic factors were that the majority were between 30 and 59 years old (50.9%), male (62.2%), mestizo (97.1%), from the district of Iquitos (22.8%) and working as independent workers (58.5%). The clinical factors were that the majority presented pulmonary tuberculosis (92.5%) and sensitive scheme (86.9%). Conclusions: The factors that were significantly associated with mortality from active tuberculosis were age, mestizo ethnicity, pulmonary tuberculosis, sensitive treatment regimen and HIV coinfection.